Biodegradable synthetic polymer in orthopaedic application: A review. (2023) - Al-Shalawi, Faisal Dakhelallah; Azmah Hanim, M.A.; Ariffin, M.K.A.; Looi Seng Kim, Collin; Brabazon, Dermot; Calin, Recep; Al-Osaimi, Maha Obaid
Highlights: Degradable synthetic polymer implants are an excellent alternative to metal implants. synthetic biopolymer implants are not needed another surgery to remove. Degradable synthetic polymer implants should be improved their properties before use in the medical field. Abstract: Every year, many people suffer from bone fractures because of accidents or diseases. Majority of these fractures are too complicated to be treated with conventional medicine and must be mended surgically using non-degradable metal inserts. Such treatment may result in refusal and protection against stress, but may also require another surgical procedure to get rid of the metal inserts. Additionally, biodegradable metals that can readily erode inside the human body come with certain complications. These aspects prompted scientists to find alternatives to metals. Some researchers began to focus on the field of polymers which have shown significant promise in replacing metals. In orthopaedics, degradable polymeric fixation appliances are being studied to substitute metallic implants, eliminating stress protection and avoiding another implant removal surgery. The new generation of bioabsorbable and degradable polymeric implants are free from toxic and mutagenic effects. Nevertheless, these implants have several issues, including mechanical stiffness and strength limitations, unfavourable tissue responses, foreign body reactions, the late response of degraded tissue, and infection due to crystallinity and hydrophobicity. This review discusses the alternative synthetic polymer implant materials available that can be employed and their properties.